ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PAKET INTERNET OPERATOR TELEKOMUNIKASI DENGAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Santriono, Refki; Roestam, Rusdianto (LPPM Universitas Dinamika Bangsa, 2019)
For android users to fulfill their needs, they certainly feel incomplete without registering internetpackages, because it is more economical in terms of financial compared to directly using regular pulses.Various operators also offer internet packages with different types in terms of quota and usage time. Andsome operators also offer quota bonuses added to internet packages that have been purchased. Most internetpackages offered are internet packages with a duration of usage a month with different prices and bonuses.Consumers are required to be observant in choosing an internet package that suits their needs andpurchasing power. So that it does not harm the consumer itself. According to the desired criteria becausethere is no objective method to decide quickly. In computer science there is a system that can assist in theselection and decision making process to produce more effective and accurate decisions. In the DecisionSupport System there are various methods, one of which is the Analitychal Hierarchy Process (AHP) method.The basic concept of this method is to find the weights of the criteria and will be compared to eachalternative. The final result is obtained from the calculation process, which is the ranking of each alternative.It is expected that the results of this study can help decision makers in determining the telecommunicationoperator's internet package selection.